Načrtovanje relacijskih podatkovnih baz z UML - Lahajnar, Sebastian (Uporabna informatika (Ljubljana), 2001)
Information systems object oriented analysis and design with UML provides alsonew methods and diagramming techniques for database design. UML concepts expressive power is much stronger than that of Entity-Relationship Diagrams we commonly use for that purpose. Due to their object techniques are perfect for designing object and object relational databases. On the other hand, relational database servers still have the leading place on the market today.
Keywords: informacijski sistemi; načrtovanje; podatkovne baze; relacijske podatkovne baze